Method for preparing asphalt concrete by using surface modified ceramsite
By surface modification of the ceramate and mixing it with SBS modified asphalt and other additives, the problem of decreasing bond strength between the ceramate and asphalt is solved, the performance of asphalt concrete is significantly improved, and the road performance specifications are met.
Patent Information
- Application Number
- CN202411807514.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The bonding strength between ceramic granules and asphalt decreases, resulting in the peeling of ceramic granules/asphalt layer, affecting traffic safety, and easily adhere to dust pollutants during construction, resulting in interface deterioration.
By preheating the ceramate, mixing it with oleic acid and coupling agent, the surface modified ceramate is preheated with SBS modified asphalt and other additives, and mixing it evenly to prepare modified ceramate asphalt concrete.
It significantly improves the interface combination performance between ceramic granules and asphalt, improves the compressive and aging resistance of asphalt concrete, improves the adhesion level, dynamic stability and residual stability, and meets the requirements of road performance specifications.
Smart Images

Figure CN119638271A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, in particular to a method for preparing asphalt concrete by utilizing surface-modified ceramsite. Background Art
[0002] As a man-made lightweight aggregate, ceramsite is increasingly used in construction projects and road and bridge construction. In addition to the advantages of ordinary asphalt concrete pavement, ceramsite asphalt concrete pavement also has the characteristics of smooth and comfortable driving, low noise, light weight and low elastic modulus. If asphalt concrete mixed with ceramsite is used in bridge pavement, it can reduce the weight of the bridge, increase the bridge's spanning capacity and service life.
[0003] Patents on ceramsite asphalt mixtures include: CN101100360A, CN101219869A and CN106007486A, etc. The ceramsite content in the disclosed technical solutions is generally less than 60%, which meets the general road performance requirements. However, in practice, it is found that the ceramsite / asphalt layer falls off on some sections of the road, which poses a serious threat to traffic safety. Rainwater invades the interior of the asphalt layer, resulting in a decrease in the bonding force between the ceramsite / asphalt interface and the structural layers. In the actual road paving process, the ceramsite will float and segregate, and will break and degrade under the rolling of the roller. The adhesion performance of ceramsite and asphalt and the degradation of gradation are particularly prominent, which has become a major obstacle to the application of ceramsite in road engineering. Optimizing the surface properties of ceramsite, enhancing its interface bonding with asphalt, optimizing the gradation of ceramsite aggregates, and improving the comprehensive mechanical properties of the space between multiple components of concrete are the key to improving the performance of ceramsite asphalt concrete.
[0004] Ceramic aggregate has a hydrophilic surface and has a general affinity with asphalt. Its porous and irregular surface reduces its bonding strength with asphalt. At the same time, dust and pollutants are inevitably adhered to it during the construction process, which easily causes the interface between it and the asphalt surface to deteriorate. By treating the surface of ceramsite with oil and adding a coupling agent, it is expected that the surface properties of ceramsite can be significantly optimized and the interfacial bonding performance between ceramsite and asphalt can be improved. Patent CN110002793A discloses an epoxy asphalt mixture mixed with ceramsite aggregate and a preparation method thereof. It uses epoxy asphalt as a binder to optimize the interfacial performance between ceramsite and asphalt, and increases the amount of ceramsite to more than 85% of the mixture. However, epoxy asphalt needs to be added in steps, the modification process is complicated, and the cost is high, so it is not conducive to engineering applications.
[0005] Through oleophilic modification and coupling agent modification, ceramsite and asphalt can be more closely combined, and its water loss resistance, adhesion and durability can be improved. In the compounding of inorganic non-metallic raw materials, coupling agents can greatly improve product performance, so coupling agents have become a research hotspot. Coupling agents generally consist of two parts: one part is an inorganic-philic group that can react with inorganic fillers or reinforcing materials; the other part is an organic-philic group that can react with synthetic resins and is a good surfactant. Since asphalt is an organic material and ceramsite is an inorganic material, coupling agents can well combine asphalt and ceramsite.
[0006] In view of the above problems, a method for preparing asphalt concrete using surface modified ceramsite is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing asphalt concrete using surface modified ceramsite. The present invention solves the problem that the bonding strength between ceramsite and asphalt decreases in the above background and dust pollutants inevitably adhere to the concrete during the construction process.
[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing asphalt concrete using surface modified ceramsite, comprising the following steps:
[0009] S1: preheating the ceramsite, adding oleic acid and stirring for 3 to 5 minutes, then adding a coupling agent and stirring for 5 to 10 minutes to obtain surface-modified ceramsite;
[0010] S2: Preheat the SBS modified asphalt and other additives, and then mix and stir them with the surface modified ceramsite to obtain modified ceramsite asphalt concrete.
[0011] Furthermore, in S1, the preheating temperature of the ceramsite is 125° C. to 140° C., and the time is 1 h to 3 h.
[0012] Furthermore, in S1 and S2, the raw materials are composed of the following in parts by mass: 70-85 parts of ceramsite, 2-5 parts of oleic acid, 1-3 parts of coupling agent, 5-10 parts of SBS modified asphalt, and 5-10 parts of other additives.
[0013] Furthermore, in S1, the ceramsite is a lightweight and high-strength ceramsite with a particle size of 3 to 6 mm or 6 to 10 mm and an apparent density of 1650 kg / m 3 ~2000kg / m 3 , barrel pressure strength is greater than 9MPa.
[0014] Furthermore, in S2, other additives include: one or more of fly ash and limestone powder, with a particle size of 45 to 147 μm.
[0015] Furthermore, in S2, other additives also include: lignocellulose.
[0016] Furthermore, in S1, the coupling agent includes: a silane coupling agent and a titanate coupling agent, wherein the mass ratio of the silane coupling agent to the titanate coupling agent is 2:1 to 4:1.
[0017] Furthermore, the silane coupling agent is selected from one or more of KH560 and KH570.
[0018] Furthermore, the titanate coupling agent is TMC-TTS.
[0019] Furthermore, in S2, the mixing and stirring temperature is 120°C to 150°C, the time is 0.5h to 1h, and the rotation speed is 100rpm to 150rpm.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. In the present invention, the ceramsite and the coupling agent are first stirred and mixed evenly, in order to make the ceramsite and other mixing materials adhere more closely; after the ceramsite is modified by the lipophilic / coupling agent, the adhesion performance is improved, so that the interface structure between it and the asphalt is optimized; its compression resistance and anti-aging performance are improved.
[0022] 2. The adhesion level of asphalt concrete has been increased by 2 levels, the dynamic stability has been increased by 40%, and the residual stability has been increased by more than 2%. The road performance meets the requirements of the specifications and improves practicality.
[0023] 3. The preparation method of expanded clay asphalt concrete consumes less additives, is green and environmentally friendly, and is suitable for engineering applications after modification. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a specific flow chart of the present invention;
[0025] Figure 2 This is the Marshall residual stability bar graph of lightweight high-strength ceramsite asphalt mixture;
[0026] Figure 3 It is a bar chart of dynamic stability of lightweight high-strength ceramsite asphalt mixture;
[0027] Figure 4 Comparison of rutting deformation data of conventional and lightweight high-strength expanded clay asphalt mixtures. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1: Reference Figure 1-Figure 4 ;
[0030] A method for preparing asphalt concrete using surface modified ceramsite comprises the following steps:
[0031] S1: preheating the ceramsite, adding oleic acid and stirring for 3 to 5 minutes, then adding a coupling agent and stirring for 5 to 10 minutes to obtain surface-modified ceramsite;
[0032] S2: Preheat the SBS modified asphalt and other additives, and then mix and stir them with the surface modified ceramsite to obtain modified ceramsite asphalt concrete.
[0033] In this scheme: 3-6 mm ceramsite, SBS modified asphalt, fly ash and limestone powder are preheated at 130°C for 2.5 hours; 70 parts of ceramsite, 1 part of oleic acid and 1 part of coupling agent are weighed; wherein the mass ratio of KH560, KH570 and TMC-TTC in the coupling agent is 1:2.2:1.3;
[0034] The coupling agent was added to the pre-impregnated ceramsite solution and mixed thoroughly to obtain the modified ceramsite; the modified ceramsite and fly ash, SBS modified asphalt, limestone powder and wood cellulose were mixed in sequence according to the mass ratio of 3:1:2:1:0.8, and stirred at 130°C and 130rpm for 1h to obtain the usable asphalt concrete. The samples were prepared and tested according to the standards of the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the results were recorded in Table 1.
[0035] Example 2: Reference Figure 2-Figure 4 ;
[0036] In S1, the preheating temperature of the ceramsite is 125°C to 140°C, and the time is 1h to 3h.
[0037] In S1 and S2, the raw materials are composed as follows by mass: 70-85 parts of ceramsite, 2-5 parts of oleic acid, 1-3 parts of coupling agent, 5-10 parts of SBS modified asphalt, and 5-10 parts of other additives.
[0038] In this scheme: 3-6mm ceramsite, SBS modified asphalt, fly ash, and limestone powder are preheated at 130°C for 2.5 hours; 80 parts of ceramsite, 2 parts of oleic acid, and 2 parts of coupling agent are weighed. Among them, the mass ratio of KH560, KH570, and TMC-TTC in the coupling agent is 1:2.5:1.5;
[0039] The coupling agent was added to the pre-impregnated ceramsite solution and mixed thoroughly to obtain the modified ceramsite; the modified ceramsite and fly ash, SBS modified asphalt, limestone powder and wood cellulose were mixed in sequence according to the mass ratio of 3:1:2:1:0.8, and stirred at 130°C and 130rpm for 1h to obtain the usable asphalt concrete. The samples were prepared and tested according to the standards of the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the results were recorded in Table 1.
[0040] Example 3: Reference Figure 2-Figure 4 ;
[0041] In S1, the ceramsite is lightweight and high-strength, with a particle size of 3-6mm or 6-10mm and an apparent density of 1650kg / m 3 ~2000kg / m 3 , the bearing strength is greater than 9MPa.
[0042] In this scheme: 6-10mm ceramsite, SBS modified asphalt, fly ash, and limestone powder are preheated at 130°C for 2.5 hours; 70 parts of ceramsite, 1 part of oleic acid, and 1 part of coupling agent are weighed. Among them, the mass ratio of KH560, KH570, and TMC-TTC in the coupling agent is 1:2.2:1.3; the coupling agent is added to the ceramsite pre-impregnation liquid and fully mixed to obtain modified ceramsite;
[0043] The modified ceramsite and fly ash, SBS modified asphalt, limestone powder and wood cellulose were mixed in a mass ratio of 3:1:2:1:0.8, and stirred at 130°C and 130 rpm for 1 hour to obtain usable asphalt concrete. Samples were prepared and tested according to the standards of the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the results were recorded in Table 1.
[0044] Example 4: Reference Figure 2-Figure 4 ;
[0045] In S2, other additives include: one or more of fly ash and limestone powder, with a particle size of 45 to 147 μm.
[0046] In S2, other additives include: wood cellulose.
[0047] In this scheme: 6-10mm ceramsite, SBS modified asphalt, fly ash, and limestone powder are preheated at 130°C for 2.5 hours; 80 parts of ceramsite, 2 parts of oleic acid, and 2 parts of coupling agent are weighed. Among them, the mass ratio of KH560, KH570, and TMC-TTC in the coupling agent is 1:2.5:1.5; the coupling agent is added to the ceramsite pre-impregnation solution and fully mixed to obtain modified ceramsite;
[0048] The modified ceramsite and fly ash, SBS modified asphalt, limestone powder and wood cellulose were mixed in a mass ratio of 3:1:2:1:0.8, and stirred at 130°C and 130 rpm for 1 hour to obtain usable asphalt concrete. Samples were prepared and tested according to the standards of the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the results were recorded in Table 1.
[0049] Example 5: Reference Figure 2-Figure 4 ;
[0050] In S1, the coupling agent includes: a silane coupling agent and a titanate coupling agent, wherein the mass ratio of the silane coupling agent to the titanate coupling agent is 2:1 to 4:1.
[0051] In this scheme: 3-6mm, 6-10mm ceramsite, SBS modified asphalt, fly ash, limestone powder are preheated at 130℃ for 2.5h; 80 parts of ceramsite, 2 parts of oleic acid, and 2 parts of coupling agent are weighed. Among them, the mass ratio of KH560, KH570 and TMC-TTC in the coupling agent is 1:2.5:1.5; the coupling agent is added to the ceramsite pre-soaking liquid and fully mixed to obtain modified ceramsite, wherein the mass fraction ratio of 3-6mm and 6-10mm ceramsite is 0.5:1;
[0052] The modified ceramsite and fly ash, SBS modified asphalt, limestone powder and wood cellulose were mixed in a mass ratio of 2.5:1:2.5:1:0.8, and stirred at 130°C and 130rpm for 1h to obtain usable asphalt concrete. Samples were prepared and tested according to the standards of the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the results were recorded in Table 1.
[0053] Example 6: Reference Figure 2-Figure 4 ;
[0054] The silane coupling agent is selected from one or more of KH560 and KH570.
[0055] The titanate coupling agent is TMC-TTS.
[0056] In this scheme: 3-6mm, 6-10mm ceramsite, SBS modified asphalt, fly ash, limestone powder are preheated at 130℃ for 2.5h; 80 parts of ceramsite, 2 parts of oleic acid, and 2 parts of coupling agent are weighed. Among them, the mass ratio of KH560, KH570 and TMC-TTC in the coupling agent is 1:2.5:1.5; the coupling agent is added to the ceramsite pre-soaking liquid and fully mixed to obtain modified ceramsite, wherein the mass fraction ratio of 3-6mm and 6-10mm ceramsite is 1:1;
[0057] The modified ceramsite and fly ash, SBS modified asphalt, limestone powder and wood cellulose were mixed in a mass ratio of 2.5:1:2.5:1:0.8, and stirred at 130°C and 130rpm for 1h to obtain usable asphalt concrete. Samples were prepared and tested according to the standards of the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the results were recorded in Table 1.
[0058] Example 7: Reference Figure 2-Figure 4 ;
[0059] In S2, the mixing and stirring temperature is 120°C to 150°C, the time is 0.5h to 1h, and the rotation speed is 100rpm to 150rpm.
[0060] In this scheme: 3-6mm, 6-10mm ceramsite, SBS modified asphalt, fly ash, limestone powder are preheated at 130℃ for 2.5h; 80 parts of ceramsite, 2 parts of oleic acid, and 2 parts of coupling agent are weighed. Among them, the mass ratio of KH560, KH570 and TMC-TTC in the coupling agent is 1:2.5:1.5; the coupling agent is added to the ceramsite pre-soaking liquid and fully mixed to obtain modified ceramsite, wherein the mass fraction ratio of 3-6mm and 6-10mm ceramsite is 1:1.5;
[0061] The modified ceramsite and fly ash, SBS modified asphalt, limestone powder and wood cellulose were mixed in a mass ratio of 2.5:1:2.5:1:0.8, and stirred at 130°C and 130rpm for 1h to obtain usable asphalt concrete. Samples were prepared and tested according to the standards of the "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", and the results were recorded in Table 1.
[0062] Comparative Example 1:
[0063] The difference between this comparative example and the above-mentioned Examples 1 to 7 is that the comparative example is not mixed and modified with any coupling agent.
[0064] Table 1 (Test results of lightweight high-strength asphalt mixture)
[0065]
[0066]
[0067] The experimental data in the table show that the asphalt concrete formed by adding SBS modified asphalt to the ceramsite aggregate modified by coupling agent can meet the requirements of a series of road performances in "JTG F40-2004 Technical Specifications for Highway Asphalt Pavement Construction". Figure 2 It can be seen that compared with conventional asphalt concrete, its rutting deformation is significantly reduced. In addition, it can be seen from the data of Examples 5 to 7 that compared with the single ceramsite particle size of Examples 1 to 4, the various indicators of the multi-level particle size compound are improved, indicating that the ceramsite particle size range has an impact on the required indicators of asphalt concrete, and multi-level compounding and multiple references can effectively improve the required indicators of asphalt concrete.
[0068] The asphalt concrete with coupling agent-modified ceramsite of the present invention has an adhesion level increased by 2 levels, a dynamic stability increased by 40%, a residual stability increased by more than 2%, and road performance meets regulatory requirements, compared with asphalt concrete without coupling agent-modified ceramsite.
[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing asphalt concrete using surface modified ceramsite, characterized in that: The following steps are involved: S1: preheating the ceramsite, adding oleic acid and stirring for 3 to 5 minutes, then adding a coupling agent and stirring for 5 to 10 minutes to obtain surface-modified ceramsite; S2: Preheat the SBS modified asphalt and other additives, and then mix and stir them with the surface modified ceramsite to obtain modified ceramsite asphalt concrete.
2. The method for preparing asphalt concrete using surface modified ceramsite according to claim 1, characterized in that: In S1, the preheating temperature of the ceramsite is 125°C to 140°C, and the time is 1h to 3h.
3. A method for preparing asphalt concrete using surface modified ceramsite according to claim 2, characterized in that: In S1 and S2, the raw materials are composed as follows by mass: 70-85 parts of ceramsite, 2-5 parts of oleic acid, 1-3 parts of coupling agent, 5-10 parts of SBS modified asphalt, and 5-10 parts of other additives.
4. The method for preparing asphalt concrete using surface modified ceramsite according to claim 3, characterized in that: In S1, the ceramsite is lightweight and high-strength, with a particle size of 3-6mm or 6-10mm and an apparent density of 1650kg / m 3 ~2000kg / m 3 , barrel pressure strength is greater than 9MPa.
5. The method for preparing asphalt concrete using surface modified ceramsite according to claim 4, characterized in that: In S2, other additives include: one or more of fly ash and limestone powder, with a particle size of 45 to 147 μm.
6. The method for preparing asphalt concrete using surface modified ceramsite according to claim 5, characterized in that: In S2, other additives include: wood cellulose.
7. The method for preparing asphalt concrete using surface modified ceramsite according to claim 6, characterized in that: In S1, the coupling agent includes: a silane coupling agent and a titanate coupling agent, wherein the mass ratio of the silane coupling agent to the titanate coupling agent is 2:1 to 4:
1.
8. The method for preparing asphalt concrete using surface modified ceramsite according to claim 7, characterized in that: The silane coupling agent is selected from one or more of KH560 and KH570.
9. The method for preparing asphalt concrete using surface modified ceramsite according to claim 8, characterized in that: The titanate coupling agent is TMC-TTS.
10. The method for preparing asphalt concrete using surface modified ceramsite according to claim 9, characterized in that: In S2, the mixing and stirring temperature is 120°C to 150°C, the time is 0.5h to 1h, and the rotation speed is 100rpm to 150rpm.
Citation Information
Patent Citations
Dredging mud ceramic granule asphalt concrete for road and preparation method thereof
CN101100360A
Porcelain granule sheet pavement material and method for paving road surface with porcelain granule sheet pavement material
CN101219869A
Porous ceramsite and asphalt concrete and application thereof
CN106007486A
Epoxy asphalt mixture doped with hydite aggregate and preparation method of epoxy asphalt mixture
CN110002793A